PENGARUH DISIPLIN KERJA, KOMITMEN KERJA, DAN KARAKTERISTIK INDIVIDU TERHADAP TOTAL QUALITY MANAGEMENT - Ervin Mardalena Mardalena (Jurnal Manajemen Bisnis Unbara, 2020)
This research was motivated by the influence of globalization, where this has an impact on human life as expressed by R. Robertson (2011) that globalization is shrinking the process of an individual and the growing awareness of the individual. This study uses the independent variable is Work Discipline (X1), Work Commitment (X2), moderating variables, namely the individual character (X¬3), and total quality management as the dependent variable (Y). Collecting data in research using questionnaires that were distributed to 72 employees of the PDAM Baturaja, educators using population. While the analysis is performed by the data processing using SPSS version 16.0 for Windows. Results of regression analysis and t test showed that the variables of work discipline commitment variable, and variable positive effect on the individual characteristics of the variable total quality management. The coefficient of determination (R2) obtained at 0.896. This means that 89.6% of the variation can be explained by the quality of their management work discipline, work commitment and individual characteristics of the remaining 10.4% of the variation is explained by other variables.